Why don’t U.S. issuers demand European fees for IPOs? - Abrahamson, M; Jenkinson, T; Jones, H (Oxford Finance, 2009)
IPO techniques have converged over the last decade, but in this paper we find that fees charged by investment banks have not. Chen and Ritter (2000) were the first to document the “7% solution” for U.S. IPOs. We find that gross spreads in the U.S. have become even more clustered at exactly 7% in the last decade. However, although the same U.S. investment banks conduct IPOs in Europe using the same methods, we find that they charge fees that are roughly 3 percentage points lower, with far greater variance across issues. If U.S. issuers had paid European fees over the last decade they would have saved around $6bn. One possible hypothesis is that more accurate pricing of IPOs in the U.S. compared with Europe compensates for the higher direct fees. However, we find the opposite to be the case. We investigate other possible explanations for the “3% wedge”, none of which is convincing. The evidence in this paper should encourage U.S. issuers to demand European fees for their IPOs.